Pelayanan Transportasi Container Untuk Ekspor Terhadap Kepuasan Shipper (Studi pada Jakarta Tanjung Priok Port Area) - Suwarjiyono (Jurnal Aplikasi Manajemen, 2013)
In export activities, maritime transport using container is a very important mode of transportation.The mode is the most well-known facility which serves at port of Tanjung Priok, Jakarta. With regard to the claims for the container Services Manager at Jakarta's Tanjung Priok Port Area to create a service that can satisfy the quality exporters (shipper). For it is still important to answer whether the perceived service provided on the services of transport container for export in Jakarta Tanjung Priok Port Area on the basis of reliability, responsiveness, assurance, empathy, and physical evidence may result in satisfaction of the shipper (the exporter)?The purpose of this research is to analysis, examination and explains influence the services, based on dimensions reliability, responsiveness, assurance, empathy, and physical evidence against customer satisfaction, and reviews and determine dimensions the services, which has important to increase customer satisfaction. The study is done at shipper that is active in 2010 and on Bugis road at Tanjung Priok Port Area as manyas 122 companies. Meanwhile, samples this research is all member population, and put their manager deal directly with that activity as respondents. Data from the scattering instrument research analyzed using structural equation unified with software Lisrel 8.80. The results showed that service quality are reflected from the reliability in providing services, responsive service, the guarantee given in the process of customer service,empathy, as well as the availability of physical infrastructure and facilities which are able to increase the satisfaction of the transportation service users in Jakarta Tanjung Priok container Port Area. Interesting finding of this research is the dimension of the guarantee in providing services is the most important element in improving customer satisfaction on the transportation service of container for export in Jakarta Tanjung Priok Port Area. Furthermore, it can be informed from the result of this study that the insurance included in the qualityof the service, the employee in their confidence in customers; security guarantees in the attitude of the transaction, polite in the service of employees and to provide services employees in knowledge is an important role in creating a service quality of excellence in transportation services container. These results indicated that the role of human resources is the key success in guarantee to produce quality of the service, which can improve the shipper satisfaction.